Investigation of Clay Type on Low Salinity Water Flooding Using a Glass Micromodel - Wei, Xuemei; Jiang, Wenchao; Zhang, Yanyu; Wang, Zhao; Li, Xiaojun; Wu, Feipeng (Frontiers in Energy Research, 2020)
Clay minerals are regarded an important factor affecting the results of low salinity water (LSW) flooding. However, the experiments on clay minerals is mainly in the qualitative stage, the mechanism of clay minerals have yet to be further researched. In this paper, four kinds of clay minerals (montmorillonite; chlorite; illite; kaolinite) were used to measure Zeta potential in different brine, made four clay minerals microscopic models to measured wetting angle in different brine, and montmorillonite and kaolinite was chosen to microscopic displacement experiments by customized micro glass etching models. The experimental results show: with the decrease of salinity of injected water, the negative zeta potential of clay minerals increases and the wetting angle decreases; Clay minerals are more sensitive to monovalent Na+ than bivalent Ca2+; The results of microscopic experiments show that LSW can effectively improve oil recovery, whether kaolinite or montmorillonite. The recovery degree of montmorillonite is better with high salinity water (HSW) and kaolinite is better with LSW. The mechanism of LSW improves kaolinite recovery factor is the change of wettability while that of montmorillonite is the increase of water phase wettability. However, a lot of droplet-like residual oil cannot be displaced in the montmorillonite roar. In oil filed production, both kaolinite-rich reservoirs and montmorillonite-rich reservoirs are suitable for LSW flooding to improve oil recovery. However, for kaolinite rich reservoirs, the lower the salinity of injected water, the water flooding results will be better. However, for montmorillonite rich reservoirs, the resistance of Jamin effect should not be ignored while the water flooding be switched to LSW.